FACTORS SUSTAINING SUCCESSFUL LONG TERM STRATEGIC SUPPLIER MANAGEMENT - NWABUIKWU, CHRISTIAN (2016)
This study set out to explore the factors and conditions that encourage long term business alliances and to determine whether buyers and suppliers in an alliance agree on these success factors and defining conditions. The findings of this study are crucial to both the buyer and supplier corporate management to guide their decisions on whether to go into a business relationship or determine the type of business relationship that would be beneficial to their respective organisations. It is hoped that this research findings will help decision makers in both buying and supplying firms to set up a process of developing and maintaining strategic alliances throughout the supply chain. One expectation is the assumption that the research findings will provide areas for further research in the measurement of alliance success. Wider research scope would be expected to include buyer and supplier responses to identification of key similarities or differences in the business partners’ perceptions which may help or hinder the alliance’s long-term success.